Cacao flower visitation: Low pollen deposition, low fruit set and dominance of herbivores. Issue 2 (5th April 2022) - Vansynghel, Justine; Ocampo‐Ariza, Carolina; Maas, Bea; Martin, Emily A.; Thomas, Evert; Hanf‐Dressler, Tara; Schumacher, Nils‐Christian; Ulloque‐Samatelo, Carlos; Tscharntke, Teja; Steffan‐Dewenter, Ingolf
Abstract: Pollination services of cacao are crucial for global chocolate production, yet remain critically understudied, particularly in regions of origin of the species. Notably, uncertainties remain concerning the identity of cacao pollinators, the influence of landscape (forest distance) and management (shade cover) on flower visitation and the role of pollen deposition in limiting fruit set. Here, we aimed to improve understanding of cacao pollination by studying limiting factors of fruit set in Peru, part of the centre of origin of cacao. Flower visitors were sampled with sticky insect glue in 20 cacao agroforests in two biogeographically distinct regions of Peru, across gradients of shade cover and forest distance. Further, we assessed pollen quantities and compared fruit set between naturally and manually pollinated flowers. The most abundant flower visitors were aphids, ants and thrips in the north and thrips, midges and parasitoid wasps in the south of Peru. We present some evidence of increasing visitation rates from medium to high shade (40%–95% canopy closure) in the dry north, and opposite patterns in the semi‐humid south, during the wet season. Natural pollination resulted in remarkably low fruit set rates (2%), and very low pollen deposition. After hand pollination, fruit set more than tripled (7%), but was still low. The diversity and high relative abundances of herbivore flower visitors limit our ability to draw conclusions on the functional role of different flower visitors. The remarkably low fruit set of naturally and even hand pollinated flowers indicates that other unaddressed factors limit cacao fruit production. Such factors could be, amongst others, a lack of effective pollinators, genetic incompatibility or resource limitation. Revealing efficient pollinator species and other causes of low fruit set rates is therefore key to establish location‐specific management strategies and develop high yielding native cacao agroforestry systems in regions of origin of cacao. Abstract : Pollination of native cacao is surprisingly understudied, even though the process is crucial for the global chocolate production. In an understudied peruvian region, we found herbivores as dominant flower visitors, and low pollen deposition.Fruit set was low when flowers were pollinated naturally (2%), but also manually (7%). Our findings highlight the need to identify cacao pollinators that deposit sufficient compatible pollen, as well as more research on the origin of low fruit set in native cacao. Abstracto: Los servicios de polinización del cacao son cruciales para la producción mundial de chocolate, pero están poco estudiados, especialmente en las regiones donde se originó la especie. En particular, sigue existiendo incertidumbre sobre la identidad de los polinizadores del cacao, la influencia del paisaje (distancia al bosque) y el manejo (cobertura de sombra) en la visita floral, y el papel que juega la deposición de polen en limitar el cuajado de los frutos. Este trabajo tuvo como objetivo mejorar el conocimiento sobre la polinización del cacao, mediante el estudio de los factores limitantes del cuajado en Perú, parte del centro de origen del cacao. Muestreamos los visitantes florales con pegamento para insectos en 20 sistemas agroforestales de cacao en dos regiones biogeográficamente distintas del Perú, a lo largo de gradientes de cobertura de sombra y distancia al bosque. Además, evaluamos la cantidad de polen y comparamos la fructificación entre flores polinizadas natural y manualmente. Los visitantes florales más abundantes en el norte de Perú fueron áfidos, hormigas y trips; en el sur fueron trips, mosquitos y avispas parasitoides. Presentamos evidencia de un aumento en las tasas de visita con condiciones de sombra media o alta (40 ‐ 95% del dosel cerrado) en el norte seco, y patrones opuestos en el sur semi‐húmedo, durante la estación húmeda. La polinización natural resultó en tasas de cuajado de frutos notablemente bajas (2%), y en una deposición de polen muy baja. Con polinización manual, la fructificación se triplicó (7%), pero siguió siendo baja. La diversidad y la alta abundancia relativa de visitantes florales herbívoros, limitaron arrojar conclusiones sobre el papel funcional de distintos visitantes florales. La notablemente baja fructificación de las flores polinizadas naturalmente e incluso manualmente, indica que otros factores no abordados limitan la producción frutal del cacao. Estos factores podrían ser, entre otros, la falta de polinizadores eficientes, incompatibilidad genética o limitación de recursos. Por lo tanto, identificar las especies de polinizadores efectivos, así como causas adicionales de las bajas tasas de cuajado de los frutos son clave para poder establecer estrategias de manejo local, así como para desarrollar sistemas agroforestales de cacao nativo de alto rendimiento en las regiones de origen del cacao.